Mexican oregano (Lippia berlandieri Schauer) oil on turkey slaughter quality - Silva-Vázquez, Ramón; García-Macías, José Arturo; Durán-Meléndez, Lorenzo Antonio; Hume, Michel E.; Méndez-Zamora, Gerardo (Ecosistemas y Recursos Agropecuarios, 2016)
The quality of slaughtered turkeys fed a diet supplemented with Mexican oregano (Lippia berlandieri Schauer) oil was investigated. Two treatments were studied. T0: control diet and T1: control diet + 400 mg kg−1 of oregano oil with 60 % carvacrol. Live weight at slaughter was di erent, with T0 weighing 11.0 kg and T1 11.89 kg, while the performance of feathers and drumstick was higher in T0 (4.33 and 3.18 % respectively). Viscera, blood, head, neck and hot and cold carcass yield did not di er between treatments (p > 0.05). Oregano oil at 400 mg kg−1 can be used in the production of turkeys to in uence slaughter quality.